The Child Health Scenario in India: An Application of Bayesian Approach - Bhattacharjee, Atanu; Nath, Dilip C.; Bhattacharjee, Dibyojyoti (International Journal of Child Health and Nutrition, 2013)
Background: The child mortality rate of a place is an indication of the basic health facility prevalent there. A place with better medical facility records low child mortality. The child mortality rate reduction is not as expected in many developing countries. In last two decades the child death rate has not been reduced significantly in India. The aim of this work is to explore the child death rate in different Indian states. Materials and Methods: The Bayesian approach has been applied to control the over dispersion due to presence of zero (i.e. no-death count) in the data set. The Zero Inflated Poisson (ZIP) has been applied to control the presence of over the Zero Inflation Distribution. The data set has been considered from Indian National Health and Family Survey (NFHS-3) conducted during 2005-2006. The women having at least one living child of age less than five years has been selected as study subjects.